Outcome of immune checkpoint inhibitors in metastatic renal cell carcinoma across different treatment lines - Resch, I; Bruchbacher, A; Franke, J; Fajkovic, H; Remzi, M; Shariat, S F; Schmidinger, M (ESMO open, 2021)
BACKGROUND: Immune checkpoint inhibitors (ICIs) have led to a paradigm change in the management of metastatic renal cell carcinoma (mRCC). Prospective trials have focused on ICI treatment in the first or second line. The aim of this analysis is to evaluate the benefit of ICI across different treatment lines. PATIENTS AND METHODS: This is a single-center retrospective study that included mRCC patients who received ICIs in various treatment lines. Objective response rates (ORR), progression-free survival (PFS) and overall survival (OS) were evaluated. RESULTS: Ninety-four patients were eligible for full evaluation. Patients were classified as International mRCC Database Consortium (IMDC) risk group categorization as good, intermediate and poor risk in 26.8%, 61.6% and 14.8% of cases, respectively. They were treated with ICI monotherapy, dual ICI therapy and ICI + tyrosine kinase inhibitor in 59%, 20% and 21% of cases, respectively. ORR, median PFS and OS for the entire cohort was 39.4%, 9.67 months [95% confidence interval (CI) 6.9-12.4 months] and 23.6 months (95% CI 13.3-33.9 months), respectively. The ORR by treatment line was 33% in first, 40.4% in the second, 35% in the third and 43.5% in the fourth line and beyond. Median PFS by treatment line was 8.6, 10.3, 7.9 and 7.23 months, respectively. The median OS was not reached in first-line treatment and was 26.2, 18.1 and 20.7 months in the second, third and fourth line and beyond, respectively. CONCLUSIONS: ICIs or ICI combinations are active in all treatment lines and should also be offered in heavily pretreated patients. Patient selection based on tumor and patient factors allows for maximal benefit from ICI-based therapies.
Keywords: renal cell carcinoma; nádory ledvin; treatment outcome; inhibitory kontrolních bodů; Carcinoma, Renal Cell; immune checkpoint inhibitors; tyrosine kinase inhibitors; Kidney Neoplasms; Retrospective Studies; retrospektivní studie; lidé; Prospective Studies; Immune Checkpoint Inhibitors; combination therapy; immunotherapy; Humans; karcinom z renálních buněk; prospektivní studie